TRAINING PROGRAM ON STREAMLINED BUSINESS PLANNING AND MANAGEMENT FOR MICRO, SMALL, AND MEDIUM ENTERPRISES (MSMEs) IN RAPAMBINOPAKA VILLAGE - Masri, Muhammad; Fitriaman; Azis Muthalib, Dzulfikri; Putera, Asrip; Rialdy Hasan, Rachmat (Jurnal Pengabdian Masyarakat Sabangka, 2026)
This community service program aims to enhance the managerial capacity of MSME actors in Rapambinopaka Village, Lalonggasumeeto District, Konawe Regency through the “Anti-Ribet Business Management” training, which emphasizes simplified and practical approaches to business planning and management. The program was carried out in four stages preparation, core training, mentoring, and evaluation using an andragogical and hands-on learning approach to ensure that the materials were easily understood and applied. The results indicate improvements in participants’ ability to prepare one-page business plans, conduct simple and regular financial recording, apply basic digital marketing strategies, and implement task division within family-operated businesses. Participants also began using financial applications and social media platforms to expand their market reach. These improvements demonstrate increased managerial understanding and independence in business operations. The program further strengthened MSME collaboration through shared learning and local business networking.